Glucose metabolism and tumour microenvironment in pancreatic cancer: A key link in cancer progression - Dong, Shi; Li, Wancheng; Li, Xin; Wang, Zhengfeng; Chen, Zhou; Shi, Huaqing; He, Ru; Chen, Chen; Zhou, Wence (Frontiers in Immunology, 2022)
Abstract: The diagnosis and treatment of pancreatic cancer is still a worldwide problem. Diagnosis lag, high invasiveness, chemical resistance, and poor prognosis are still the bottlenecks that we cannot break through. The concept of metabolic reprogramming has broken this deadlock. There is increasing evidence that metabolic processes such as glucose, amino acids, and lipids provide continuous nutrition for the survival, proliferation, and invasion of pancreatic cancer, especially glucose metabolism, which involves the key regulation of tumour microenvironment (TME). Not only that, the crosstalk between glucose metabolism and TME also plays an important role in the targeted therapy, chemoresistance, radiotherapy ineffectiveness, and immunosuppression of pancreatic cancer. Gaining insights into the interaction of altered metabolism with the TME has emerged as a key mechanism regulating pancreatic cancer progression. This review aims to reveal the link between TME, glucose metabolism and pancreatic cancer, and is expected to provide a new direction for combination therapy of pancreatic cancer from the perspective of metabolism.